Penentuan Pemilihan Operator Seluler dengan Metode Analisis Efektifitas - Edy Suhartono; Bambang Sri Wibowo (Universitas Proklamasi 45 Yogyakarta, 2017)
This study aims to examine the influence of advertising in print media, electronic media, and social media to consumer decisions in choosing Telkomsel cellular operators, the magnitude influence of each independent variable and the most dominant variable influence the consumer decisions. This study explains the relationship between research variables through hypothesis testing. The data collection method in this research is survey with questionnaire tools. Population in this research is all of the consumer of Telkomsel cellular operator. The quantity of sample used in this research is 40 respondents. Hypothesis testing uses multiple regression analysis. Based on the results of data analysis in this research indicate that the variables of print media, electronic media, and social media influence to consumer decisions. The magnitude of influence of print media is 7%, electronic media 27.7%, and social media 41.1%. The most dominant influence of the variable is the print media variable.